Trade-Off Decisions in Distribution Utility Management - Slavickas, Anthony Rimas (My University, 1998)
As a result of the "unbundling" of traditional monopolistic electricity generation and transmission enterprises into a free-market economy, a power distribution utilities are faced with very difficult decisions pertaining to electricity supply options and quality of service to the customers. The management of distribution utilities has become increasingly complex, versatile, and dynamic to the extent that conventional, non-automated management tools are almost useless and obsolete. This thesis presents a novel and unified approach to managing electricity supply options and quality of service to customers. The technique formulates the problem in terms of variables, parameters, and constraints. An advanced Mixed Integer Programming (MIP) optimization formulation is developed together with novel, logical, decision-making algorithms. These tools enable the utility management to optimize various cost components and assess their time-trend impacts, taking into account the intangible issues such as customer perception, customer expectation, social pressures, and public response to service deterioration. The abovee concepts are further generalized and a Logical Proportion Analysis (LPA) methodology and associated software have been developed. Solutions using numbers are replaced with solutions using words (character strings) which more closely emulate the human decision-making process and advance the art of decision-making in the power utility environment. Using practical distribution utility operation data and customer surveys, the developments outlined in this thesis are successfully applied to several important utility management problems. These involve the evaluation of alternative electricity supply options, the impact of rate structures on utility business, and the decision of whether to continue to purchase from a main grid or generate locally (partially or totally) by building Non-Utility Generation (NUG).
Keywords: Electrical and Computer Engineering; Electrical and Computer Engineering